Objectives, Thursts and Macro-Dimensions of the Eighth Plan - 1992-97 (Directional Paper) - Planning Commission (Planning Commission Government of India, 1991)
The Eighth Five Year Plan (1992-1997) presents a strategic blueprint for India’s economic and social development in the context of global changes, including the end of the Cold War and international economic reforms. The plan emphasizes achieving near full employment, controlling population growth, universalizing elementary education, improving rural healthcare, and ensuring food security through agricultural diversification. It targets robust infrastructure development across energy, transport, and communication sectors to support sustainable growth. While India experienced an average economic growth of 5.5% during this period, fiscal imbalances, rising inflation, and increasing external debt posed significant challenges. Policy measures focused on currency adjustments, industrial liberalization, and promoting private sector participation, coupled with decentralization and enhanced people’s participation in governance. The plan adopts a four-fold strategy: prioritizing investments, allocating resources efficiently, creating social security networks, and strengthening delivery mechanisms to reach vulnerable populations. Macro-level projections include annual GDP growth of 5.6–6.0%, employment creation in agriculture, non-farm rural sectors, and services, and sustainable infrastructure expansion. The Eighth Plan underscores balancing economic growth with environmental sustainability, promoting inclusive development, and modernized governance to enhance India’s resilience to domestic and global challenges.
Planning Commission New Delhi December 1991
Keywords: Economic Growth; Employment Generation; Population Control; Education; Healthcare; Agriculture Development; Infrastructure; Fiscal Reforms; Export Promotion; Social Security; Environmental Sustainability; Decentralization